PENGARUH PEMBERIAN JAGUNG KUNING FERMENTASI DENGAN SUPLEMENTASI POLYUNSATURATED FATTY ACID (PUFA) DAN L-KARNITIN TERHADAP DAYA TETAS TELUR PUYUH - Ayu Siswoyo Putri; Sudibya (Sudibya); Ratih Dewanti (Faculty of Animal Science, Universitas Gadjah Mada, 2015)
The aim of the research was to evaluate the effect of feeding fermented yellow corn with polyunsaturated fatty acid and L-Karnitin supplementation on the hatchability of quail (Coturnix-coturnix japonica) egg. A number of 160 female and 40 male quails of 70 days old were used as experimental animal. The present research was designed in oneway Completely Randomized Design (CRD) with five treatments and four replication, each replication contains of eight female and two males quails. The dietary treatments were P0= basal diet, P1= P0 with 100% substitution at yellow corn by fermented yellow corn, P2= P1 + 10 ppm L-karnitin, P3= P2 + 4% tuna fish oil, P4= P2 + 4% lemuru fish oil. Suplementation of fish oil as polyunsaturated fatty acid source and L-karnitin in fermented yellow corn diet didn’t affect eggs fertility, hatchability, and hatching quality, however, it significantly (P<0.01) affected hatching weight. The best result achieved in treatment P1 because it content yellow corn fermentation which increased the weight of hatching. It can be concluded that feeding fermented yellow corn with supplementation of polyunsaturated fatty acid source and L-karnitin quail eggs, increase DOQ hatching weight of quail eggs.(Key words: Fermented yellow corn, Hatchability, L-karnitin, Polyunsaturated fatty acid, Quail)